The origin of Beliar in Sibylline Oracle 3.63: A new proposal - Kusio, Mateusz (Journal for the study of the pseudepigrapha, 2020)
This article investigates Sibylline Oracle 3.63 which states that Beliar will come ἐκ Σεβαστηνῶν, "from the Sebastenoi." Scholars have understood the verse as meaning that Beliar will be either a Roman imperial figure or a Samaritan false prophet. Pointing out the serious shortcomings of these hypotheses, the article argues that the Sibylline Beliar should be seen as originating in Asia, most probably in Phrygia or northern Galatia. The relevant numismatic and epigraphic evidence is explored along with references to those regions across the Sibylline Oracles. New interpretative possibilities generated by the proposal are also presented along with the suggestion that Sib. Or. 3.63-74 should be dated sometime between mid-first and mid-third century C.E. and provenanced to central Asia Minor.